2006
DOI: 10.1002/bdm.515
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of the angry decision maker: how appraisal tendencies shape anger's influence on cognition

Abstract: This paper reviews the impact of anger on judgment and decision making. Section I proposes that anger merits special attention in the study of judgment and decision making because the effects of anger often diverge from those of other negative emotions. Section II presents an Appraisal-Tendency Framework for predicting and organizing such effects. Section III reviews empirical evidence for the uniqueness of anger's relations to judgment and decision making. Section IV connects the Appraisal-Tendency Framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
587
8
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 791 publications
(661 citation statements)
references
References 119 publications
35
587
8
10
Order By: Relevance
“…2 In the last few decades, an increasing number of scholars have examined the effects of affect on individuals' decisions (e.g. Forgas, 1995;Isen, 1993;Lerner and Keltner, 2000;Lerner and Tiedens, 2006). A large part of this literature has focused on the consequences of experiencing specific emotions (e.g., anger, fear, happiness).…”
Section: Effect Of Weather On Affect and Cognitionmentioning
confidence: 99%
“…2 In the last few decades, an increasing number of scholars have examined the effects of affect on individuals' decisions (e.g. Forgas, 1995;Isen, 1993;Lerner and Keltner, 2000;Lerner and Tiedens, 2006). A large part of this literature has focused on the consequences of experiencing specific emotions (e.g., anger, fear, happiness).…”
Section: Effect Of Weather On Affect and Cognitionmentioning
confidence: 99%
“…Such an interpretation would be consistent with psychological research on anger and punishment. For instance, people tend to act on anger whether it is rational or not to do so (Lerner & Tiedens 2006). Brain imaging studies show that people may derive personal satisfaction from punishing others (de Quervain et al 2003;Singer et al 2006).…”
Section: Reasons For and Against Restrictive Rulesmentioning
confidence: 99%
“…Given that benefits bring information about the relationship motivations of the benefactor (Ames, Flynn, & Weber, 2004), we suggest an additional critical appraisal for the emotion of gratitude that is interpersonal in nature: perceived responsiveness to the self (Reis, Clark, & Holmes, 2004 (Schwarz & Clore, 2007) in line with emotionrelevant appraisals (Lerner & Tiedens, 2006), then considering the relational implications of gratitude is essential for understanding its role in social life. As a first step, we recently found that gratitude was uniquely associated with a reappraisal of the benefactor's positive qualities and promoted relationship-enhancing motivations toward the benefactor (Algoe & Haidt, 2008).…”
Section: Introductionmentioning
confidence: 99%